The first record of two non-native ambrosia beetles in Slovenia: Ambrosiodmus rubricollis (Eichhoff, 1875) and Ambrosiophilus atratus (Eichhoff, 1875) (Coleoptera: Curculionidae, Scolytinae) - Hauptman, Tine; Piškur, Barbara; Faccoli, Massimo; Rekanje, Blaž; Marinč, Andraž; Jurc, Maja (Zootaxa, 2019)
In September 2017, during the monitoring of the non-native ambrosia beetle Xylosandrus germanus (Blandford, 1894), one specimen of an unknown ambrosia bark beetle species was collected in Slovenia. The specimen was trapped in an ethanol-baited trap located in Klavže (46° 09´ 39˝ N, 13° 48´ 7˝ E), in the western part of Slovenia. The most characteristic feature distinguishing the specimen from other known ambrosia beetle species occurring in Slovenia was the asperities that covered the entire surface of the pronotum. Based on the scientific literature concerning the non-native bark and ambrosia beetles in Europe (Kirkendall & Faccoli 2010) and illustrated identification keys (Rabaglia et al. 2006; Faccoli et al. 2009), we identified the beetle by its morphological characteristics as Ambrosiodmus rubricollis (Eichhoff, 1875). As a result of this find, a specific monitoring was set up in 2018 in Slovenia with the aim to improve the knowledge about occurrence and distribution of A. rubricollis in this country.